Algorithm оf Computer Model Realization оf High-Frequency Processes in Switchgears Containing Non-Linear Over-Voltage Limiters - Ye. V. Dmitriev; A. M. Gashimov; N. R. Babayeva (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Analysis of the Over-Voltage Limiter (OVL) influence on electromagnetic high-frequency over-voltages at commutations with isolators of unloaded sections of wires and possibility of application of a frequency-dependent resistor in case of necessity to facilitate OVL operation conditions is provided in the paper.It is shown that it is necessary to take into account characteristics of OVL by IEEE circuit and its modifications at computer modeling of high-frequency over-voltages.